Evolving SME banking in Bangladesh : through BRAC bank ltd. and its comparison with other four banks - Nayar, Farieza (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.